A dopamine-doped BP@Sr-modified zirconia implant and its application
By modifying the dopamine-doped BP@Sr coating on the surface of zirconia bioceramics, the problem of insufficient osteogenesis induction and antibacterial performance in oral transplantation is solved, and the effect of significantly improving its osteogenesis induction and antibacterial performance is achieved.
Patent Information
- Application Number
- CN202411473587.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-04-01
AI Technical Summary
The existing zirconia bioceramics have problems with insufficient osteogenic induction ability and antibacterial performance in the field of oral transplantation.
Dopamine-doped BP@Sr coating is used to improve the biological activity of zirconia through the high adhesion of dopamine, and improve its osteogenic induction and antibacterial properties through modification of strontium ion and black phosphorus nanosheets.
It significantly improves the osteogenic induction ability and antibacterial properties of zirconia bioceramics, and enhances its clinical applicability and research value in orthopedic and dental implantation equipment.
Smart Images

Figure CN119733105A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of oral implants, and in particular to a dopamine-doped BP@Sr-modified zirconia implant and an application thereof. Background Art
[0002] Zirconia (ZrO2) is a bioceramic. Due to its aesthetic performance such as similar color and appearance to human teeth, as well as mechanical properties such as high strength and bending resistance, more and more dentists and patients choose this type of implant for restorative treatment after edentulous ...
[0003] In recent years, various approaches and methods have been used for surface modification of zirconia implants, including physical and chemical treatment, bio-coating modification, ultraviolet irradiation, etc. Dopamine and polydopamine (PD) are highly biocompatible coatings that can be prepared on the surface of zirconia by physical deposition (immersion). Dopamine bio-coatings have been shown to promote the proliferation of human gingival fibroblasts (hGFs), the expression of fibronectin, integrin β1 and the secretion of type 1 collagen, and enhance the surface bioactivity of zirconia by increasing the filopodia of cells and improving early cell adhesion. In the long run, this method is suitable for the initial treatment of bio-multifunctional strategies for orthopedic and dental implants.
[0004] Strontium ion (Sr 2+) is one of the essential trace elements for the human body and is also an element related to bone formation. 90% of strontium ions in the human body are present in bones and teeth. Strontium and strontium ranelate are often used to treat osteoporosis. Strontium ions can inhibit the activity of osteoclasts by stimulating signaling pathways such as OPG / RANKL / NFκB, thereby reducing bone resorption; secondly, it can also enhance the activity of alkaline phosphatase (ALP) in osteoblasts and the expression of osteoblast markers such as bone sialoprotein (BSP) and osteocalcin (cyanate), which gives it a highly efficient osteogenic effect. Wu et al. added strontium ions to calcium phosphate mixed cement and found that compared with pure calcium phosphate cement, its alkaline phosphatase activity was significantly increased after 4 and 7 days of osteogenic induction. LEE et al. reported that nano bone cements doped with strontium ions can significantly stimulate the bone regeneration ability of pre-osteoblasts, inhibit osteoclasts, and reduce bone resorption. At the same time, bone integration is usually accompanied by the formation of new blood vessels, and strontium ions also have the function of promoting angiogenesis. Therefore, modifying strontium ions on implantable devices has become a widely used strategy.
[0005] Black phosphorus nanosheets (BPNSs) are the "new stars" in two-dimensional (2D) materials. They are obtained by peeling black phosphorus (BP). They have unique biological activity, combined with biodegradability and excellent biocompatibility, and have attracted widespread attention in the biomedical field. Black phosphorus can form phosphates when degraded in situ, and form calcium phosphate with calcium in the body, which is a crucial component for osteogenesis. In addition, black phosphorus has a high near-infrared (NIR) photothermal conversion efficiency and the function of generating reactive oxygen species, so it is suitable for photothermal therapy (PTT) and photodynamic therapy (PDT) to conduct research on combating bacteria, inhibiting inflammation and treating tumors. Combined with the antibacterial properties and osteogenic potential of black phosphorus, it may be suitable for modifying the surface of implants to promote bone integration and reduce bacterial biofilm formation.
[0006] Currently, it is difficult to improve osteogenic induction and enhance anti-bacterial infection performance on the relatively inert surface of zirconia bioceramics. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to improve the osteogenic induction ability and antibacterial properties of the surface of zirconia bioceramics. To achieve the above-mentioned purpose, the present invention provides an osteogenic and antibacterial dopamine-doped BP@Sr coating, wherein the dopamine-doped BP@Sr coating is used to modify inert interventional medical devices, and the preparation method of the dopamine-doped BP@Sr coating is as follows:
[0008] (1) preparing a 0.1-5 mg / ml dopamine solution, adjusting its pH to alkaline, and completely immersing an inert interventional medical device in the dopamine solution for 24 hours to form a polydopamine coating on the surface of the inert interventional medical device;
[0009] (2) immersing the inert invasive medical device modified with the polydopamine coating in a mixed solution of 50 wt % polyallylamine and NaOH for 12 h to perform amino-rich modification;
[0010] (3) adding a strontium salt solution of the same volume ratio and immersing for 12 hours to fix the strontium ions on the surface of the dopamine coating;
[0011] (4) Prepare 0.1-1.5 mg / mL -1 Black phosphorus suspension, immersing the coating obtained in step (3) in the black phosphorus suspension, treating in a vacuum negative pressure drying oven for 6 hours, loading black phosphorus nanosheets through strong electrostatic bonding, and obtaining the dopamine-doped BP@Sr coating.
[0012] Preferably, the mass concentration of NaOH is 2-10 mg / ml, and further, the mass concentration is preferably 6 mg / ml.
[0013] Preferably, the step (1) can be repeated 1-9 times to prepare 2-10 layers of polydopamine coating.
[0014] Preferably, the concentration of the dopamine solution is 1 mg / ml.
[0015] Preferably, the pH of the dopamine solution is adjusted to 8-10, preferably to 9.
[0016] Preferably, the strontium salt comprises one or more of strontium chloride, strontium bromide, strontium iodide and strontium nitrate, preferably strontium chloride.
[0017] Preferably, the mass concentration of the strontium salt is 5-40 mg / ml, preferably 20 mg / ml.
[0018] Preferably, the concentration of black phosphorus is 0.5 mg / mL -1 .
[0019] Preferably, after steps (1), (3) and (4), the product is ultrasonically washed three times with one or more of anhydrous ethanol, acetone and deionized water, and then dried for later use.
[0020] In a preferred embodiment of the present invention, the present invention provides an inert interventional medical device, wherein the inert interventional medical device is modified by a dopamine-doped BP@Sr coating.
[0021] Preferably, the interventional medical device is a dental implant, an artificial joint, an artificial heart valve or an interventional cardiovascular stent, preferably a dental implant.
[0022] Preferably, the material of the dental implant is pure titanium, titanium alloy, zirconium oxide or carbon, preferably zirconium oxide.
[0023] In another preferred embodiment of the present invention, the present invention provides the use of the dopamine-doped BP@Sr coating of the present invention in the preparation of osteogenic and antibacterial products.
[0024] The present invention designs a dopamine-doped Sr on the surface of zirconium oxide bioceramics. 2+ Bio-multifunctional coating with black phosphorus nanosheets (BP@Sr). The high adhesion of dopamine can improve the biological inertness of zirconium oxide itself. It also improves the hydrophilicity and roughness of the sample, thereby promoting the adhesion and proliferation of osteoblasts on its surface, and making zirconium oxide have a certain photothermal effect and excellent resistance to bacterial microbial infection. It has potential clinical applicability and research value in orthopedic and dental implant devices.
[0025] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of zirconia bioceramics coated with dopamine-doped BP@Sr and its photothermal superiority / osteogenesis induction / bacterial inhibition performance.
[0027] Figure 2 These are the FE-SEM and TEM results: (A) electron microscope image of black phosphorus nanosheets after ultrasonic liquid phase exfoliation; (B) transmission electron microscope image of black phosphorus nanosheets; (C) electron microscope images of Control, PDPA, Sr, BP, and BP@Sr group sample materials.
[0028] Figure 3 Photographic images and quantitative analysis of water contact angles of Control, PDPA, Sr, BP, and BP@Sr groups; confidence coefficients were set at 95% (*<0.05) and 90% (**<0.01), respectively.
[0029] Figure 4 It is the surface element distribution analysis result diagram of Control, PDPA, Sr, BP and BP@Sr groups.
[0030] Figure 5 (A) The concentration curve of the cumulative release of Sr2+ of the Sr experimental group samples at 0, 1, 3, 7, 14, and 21 days; (B) The Zeta potential analysis results of black phosphorus nanosheets.
[0031] Figure 6 The results of photothermal analysis are as follows: (A) The highest temperature of each group of samples in a dry environment under NIR irradiation; (B) The highest temperature of each group of samples immersed in PBS under NIR irradiation; (C) After surface modification with black phosphorus nanosheets of different concentrations, the samples were immersed in PBS and had the highest temperature under NIR irradiation; (D) The temperature rise curve of each group of samples under dry conditions; (E) Photothermal stability test of the BP@Sr group with five on / off cycles; (F) Photothermal images of each group; The confidence coefficients were set to 95% (*<0.05) and 90% (**<0.01), respectively.
[0032] Figure 7 (A) Representative images of MC3T3-E1 cell morphology (blue / green: nucleus / cytoskeleton); (B) Cell viability on the fourth day; (C) Cell viability on the seventh day; the confidence coefficients were set at 95% (*<0.05) and 90% (*<0.01), respectively.
[0033] Figure 8 These are live-dead staining images of MC3T3-E1 cells on the third and seventh days.
[0034] Fig. 9 (A) BCIP / NBT alkaline phosphatase colorimetric images of MC3T3-E1 cells; (B) ALP (day 4) activity; (C) ALP (day 7) activity; the confidence coefficients were set at 95% (*<0.05) and 90% (*<0.01), respectively.
[0035] Fig.10 Results of mineralization and osteogenic gene expression experiments, (A) ARS staining and mineralized nodule images of each experimental group at 21 days; (B) Quantitative analysis of mineralization; (C) Relative expression of osteogenic genes (ALP, RUNX2) in Control, Sr, BP and BP@Sr groups; confidence coefficients were set at 95% (*<0.05) and 90% (*<0.01), respectively.
[0036] Fig.11 Staphylococcus aureus was co-cultured with Control, PDPA, Sr, BP, and BP@Sr materials for 4 h. (A) Plate counting images of each group under NIR(-) and NIR(+) treatments; (B) Quantitative analysis of colony counts without NIR treatment; (C) Quantitative analysis of colony counts under NIR(+) treatment; confidence coefficients were set at 95% (*<0.05) and 90% (*<0.01), respectively.
[0037] Fig.12Escherichia coli was co-cultured with Control, PDPA, Sr, BP, and BP@Sr materials for 4 h. (A) Plate counting images of each group under NIR(-) and NIR(+) treatments; (B) Quantitative analysis of colony counts without NIR treatment; (C) Quantitative analysis of colony counts under NIR(+) treatment; confidence coefficients were set at 95% (*<0.05) and 90% (*<0.01), respectively.
[0038] Fig.13 (A) Electron microscopic morphology of Staphylococcus aureus and control and BP@Sr experimental group materials after co-culture for 4 hours under NIR(-) and NIR(+) treatments; (B) Electron microscopic morphology of Escherichia coli bacteria under the same treatment as above.
[0039] Fig.14 These are bacterial live-dead staining images of Staphylococcus aureus and Escherichia coli after being incubated with each group of samples for 4 hours and then treated with NIR(+). DETAILED DESCRIPTION
[0040] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0041] Experimental Materials
[0042] Table 1 Experimental reagents and materials
[0043]
[0044] Table 2 Main instruments and equipment
[0045]
[0046] Example 1 Preparation of Zirconia BP@Sr Coating
[0047] 1. Zirconia substrate preparation and pretreatment
[0048] First, the untreated MT-10 zirconia ceramic block was cut into square thin blocks with a thickness of 1.85 mm, a width of 10.35×10.35 mm, and uniform thickness by wire cutting with a cutting machine. Then, after being treated at 900 degrees in a high-temperature sintering furnace, it was sintered into a bioceramic block with high mechanical strength and hardness. Then, the surface of the zirconia was polished and polished with 400, 600, 800, 1000, and 2000 mesh silicon carbide sandpaper to make it smooth and flat. The treated zirconia sheet was ultrasonically cleaned for 15 minutes (ultrasonic frequency was 100 Hz) with acetone, anhydrous ethanol, and deionized water in turn to remove surface impurities and other contaminants. Then it was dried for use.
[0049] 2. Preparation of black phosphorus nanosheets (BPNSs)
[0050] Take an appropriate amount of black phosphorus (BP, vacuum-protected from light and dry storage) and place it in a round-bottom centrifuge tube, add about 20 mL of N-methylpyrrolidone (1-Methyl-2-Pyrrolidinone, NMP), the main function of which is to prevent BP from direct contact with air and better disperse the black phosphorus flakes. Take another large beaker filled with ice water, fix the round-bottom centrifuge tube in the beaker with a rack, and fix it with tape to prevent the round-bottom centrifuge tube from shifting.
[0051] The entire process of stripping the black phosphorus sheet must be carried out under vacuum, light-proof, and ice-water bath conditions. Install the coarse probe (probe diameter 6mm) on the integrated ultrasonic crusher, adjust the mode to the corresponding probe size and start working, set the power to 70%, and set the machine temperature to 20°C. The on / off cycle time is: 3s / 2s, and the single duration of ultrasonic liquid phase stripping is 1h, for a total of 15 times. Replace the ice water after each completion to prevent long-term work and probe heating from affecting the instrument itself, samples in the container, etc. After completing the operation once, place it in an ordinary ultrasonic cleaning machine under ice bath conditions and work the same number of times and time to obtain the product with maximum efficiency.
[0052] The peeled black phosphorus suspension is placed in a centrifuge again and centrifuged at 3500rpm for 30min. After centrifugation, the precipitate is removed, and then 1mL of the upper liquid is taken out and placed in an EP tube. After adding several tubes, continue to centrifuge at 13500rpm for 10min in an ultra-high-speed refrigerated centrifuge. After centrifugation, carefully remove the supernatant and keep the precipitate. Disperse the precipitate in anhydrous ethanol and continue to wash twice at (135000rpm, 10min), then disperse it in deionized water and wash twice in the same way. The final product can be obtained. After centrifugation, the EP tube containing the black phosphorus dispersion suspension is initially frozen, placed in a vacuum freeze dryer and freeze-dried for 48h, and taken out for use. The uncentrifuged black phosphorus suspension is stored at 4°C in a dark, vacuumed or sealed state for later use.
[0053] 3. Preparation of Zirconia BP@Sr Coating
[0054] First, evenly spread the prepared zirconium oxide sheet in a culture dish with the front side facing up. Then immerse it in a 1mg / ml dopamine solution (PH=9) and cover the zirconium sheet. Soak it for 24 hours in a dark environment. Wait for it to polymerize to form a polydopamine coating. Then discard the liquid and soak it again for the same time in the same way. After the time is up, wash the soaked sample three times with anhydrous ethanol, acetone, and deionized water ultrasonically, dry it, and store it in a dark environment for later use.
[0055] The prepared polydopamine coating sample was immersed in a mixed solution system of poly(allylamine) solution (50wt%) and NaOH (6mg / ml). After soaking for 12 hours, the prepared sample was named PDPA group. The same volume ratio of anhydrous strontium chloride solution (20mg / ml) was added and soaked for 12 hours and named Sr group. After soaking, ultrasonic cleaning and drying were performed for use. Then the prepared black phosphorus suspension (concentration of 0.5mg / mL-1) was added to the above two groups of samples respectively. In a vacuum negative pressure drying oven, it was treated for 6 hours to load black phosphorus nanosheets through strong electrostatic binding. And they were named: BP group, BP@Sr group. After preparation, ultrasonic cleaning was performed to remove black phosphorus nanosheets that were not firmly bound to the surface. Finally, the samples were stored under vacuum conditions and dried away from light for use.
[0056] Figure 1 A schematic diagram of the preparation of zirconium oxide BP@Sr coating and its photothermal superiority / osteogenesis induction / bacterial inhibition performance is shown.
[0057] Example 2 Characterization of Zirconia BP@Sr Coating
[0058] 1. Field Emission Scanning Electron Microscope (FE-SEM) Analysis
[0059] Field emission scanning electron microscope has the advantages of ultra-high resolution, secondary electron image and reflected electron image observation of different solid objects, and subsequent image processing. In this experiment, a few drops of the peeled black phosphorus suspension were diluted and dispersed in 2ml of anhydrous ethanol, and then 10μL was aspirated and dropped on the silicon wafer, and placed in a vacuum drying oven for the liquid to evaporate. After the samples of each experimental group were prepared, they were thoroughly cleaned and dried and placed in a vacuum ion sputtering instrument together, and gold was sprayed on the sample surface with a discharge current of 8mA for 1 minute. Then the surface morphology of the black phosphorus nanosheets on the silicon wafer and the size of the coating load of each group of samples were observed under the microscope, and the pictures were collected and measured with Image J.
[0060] like Figure 2 As shown in Figure A, the black phosphorus nanosheets after ultrasonic liquid phase treatment are diluted and evenly dispersed on the silicon wafer. Through field emission scanning electron microscopy, it can be observed that most of the black phosphorus sheets are nanoscale in size, with a size between 400-500nm and below. There is no obvious heavy layer or thick layer phenomenon. At the same time, Figure 2As shown in Figure C, observation of each group of samples shows that: the Control group material (simply sintered zirconia without any other treatment) shows a relatively smooth surface with scattered pits. The surface of the PDPA group material is not as smooth as the Control group due to the attachment of dopamine / polydopamine particles and the presence of -NH2, and is slightly rough. The Sr group material has obvious strontium ball particles of varying sizes attached, with diameters ranging from about 1-2 microns to several microns. The black phosphorus nanosheets in the BP group material are modified to the zirconia surface through the adhesion of dopamine / polydopamine and the electrostatic bonding of -NH2, and can be observed to be scattered. It can be observed from the electron microscope image of the BP@Sr group that, in addition to the base material, black phosphorus nanosheets are also scattered on the surface of the strontium ball particles.
[0061] 2. Transmission electron microscopy (TEM) analysis
[0062] First, the sample is diluted to an ideal multiple, then dropped onto a thin copper sheet and vacuum dried overnight. Then, an accelerated and focused electron beam is projected onto the black phosphorus nanosheet sample through a transmission electron microscope, where it collides with atoms on the sample and changes direction, thereby generating stereoscopic angle scattering for imaging. After taking the picture, Image J is used to analyze the diameter and thickness of the peeled black phosphorus nanosheet.
[0063] like Figure 2 As shown in Figure B, two-dimensional ultrathin black phosphorus nanosheets were successfully prepared by ultrasonic liquid phase exfoliation. The size of the nanosheets was consistent with the FE-SEM results through analysis and measurement.
[0064] 3. Water contact angle (WCA) measurement
[0065] In this experiment, the SDC-200S contact angle tester of Dongguan Shengding Precision Instrument Co., Ltd. was used to test each group of samples. The drop angle measurement method was used during the measurement process. 5μL of ultrapure water was dripped vertically on the sample surface, and a high-speed camera was used to capture the image of the moment when the liquid contacted the sample surface. Each group was set up with 15 parallel samples for repeated testing of the experiment. After the results were measured, the size of the contact angle of each group was analyzed by statistical software.
[0066] Figure 3The water contact angle test results of the sample materials of the Control, PDPA, Sr, BP, and BP@Sr experimental groups are shown. From the high-speed photography captured images and further quantitative analysis of the contact angle measurement, it can be preliminarily known that the Control group has the highest WCA value (~77.2°). With the addition of dopamine / polydopamine / -NH2 coating and strontium ions, the WCA shows a downward trend. The water contact angle values of the PDPA group and the Sr group were measured as: (~59.1°) and (~48.4°), respectively; and after the above two groups of materials were encoded and loaded with black phosphorus nanosheets, the hydrophilicity of the materials was more obvious, and the WCA decreased to (~36.8°) and (~19.7°) respectively. Through this experiment, it can be obtained that compared with the simple sintered zirconia bioceramics without other treatments, the hydrophilicity of the material is significantly increased by doping the BP@Sr coating with dopamine (p**<0.01).
[0067] 4. X-ray energy dispersive spectrometer (EDS) analysis
[0068] The pre-treatment of this test is the same as that of FE-SEM. That is, the measurement is performed after sufficient drying and gold spraying. EDS analyzes the composition and corresponding content of various elements by generating corresponding X-ray characteristic wavelengths during the test process for various elements contained on the surface of the test material. Through this experiment, the main element composition, content ratio and possible changes of zirconia bioceramics, as well as its coating and modification can be tested.
[0069] The contents of the main elements (C, N, P, Sr) of the five materials in the control, PDPA, Sr, BP, and BP@Sr groups are as follows Figure 4 As shown in the X-ray spectrum analysis, the Control group shows obvious characteristic peaks of Zr elements, and the C element is mainly visible. The N element begins to appear in the PDPA group. The Sr and P elements only occupy the surface of the Sr and BP groups. The Sr and P elements occupy the main components of the surface of the BP@Sr group.
[0070] 5. Inductively coupled plasma optical emission spectrometer (ICP-OES) detection of Sr 2+ concentration
[0071] ICP-OES can measure the ppm-level element content in the solution, and based on this, the content of a certain ion released by the sample within the number of days to be tested can be qualitatively and quantitatively analyzed; in this experiment, this method was used to determine the cumulative release of strontium ions in the sample coating. The specific method is as follows: Phosphate buffer (PBS) is often used to simulate the physiological liquid ion environment in the body. The Sr group samples were immersed in 5mL PBS solution (PH=7.4) at a constant temperature of 37°C for 1, 3, 7, 14, and 21 days. The extract was taken out regularly at the set soaking time. After each extraction, the same volume of fresh PBS solution was added. And it was stored in a -20°C refrigerator. After 21 days of soaking, the Sr released on each day was tested and measured. 2+ concentration.
[0072] from Figure 5 AObservation shows that Sr in the Sr group 2+ It was released rapidly on the first day, and then released on the seventh day. After that, the release rate gradually became slow, and the maximum release amount was reached on the 21st day. According to the cumulative release curve, the Sr of the Sr experimental group material 2+ The total release concentration was approximately 10.15±0.03ppm.
[0073] 6. Zeta potential test of black phosphorus nanosheets
[0074] Zeta potential can test the electrostatic potential of suspended particles in liquid close to the surface. In order to test the surface charge of the black phosphorus nanosheets we prepared and prepare for subsequent processing. First, the prepared black phosphorus nanosheets were fully ultrasonicated, and then gradiently diluted after they were sufficiently dispersed, and then placed in the Malvern particle size analyzer for measurement. Dilute to the ideal multiple and test the potential.
[0075] Figure 5 B is the surface potential of the prepared black phosphorus nanosheets. According to the measurement results, it can be seen that the black phosphorus nanosheets are negatively charged.
[0076] 7. Analysis and recording of photothermal properties of black phosphorus nanosheets
[0077] Black phosphorus nanosheets have a high photothermal conversion efficiency. In order to verify that the material we prepared also has this function, we selected a near-infrared laser (NIR) 808nm excitation and set the power to 1W / cm 2, the irradiation time is 10min. Then the samples to be tested in each experimental group are placed at room temperature and in an environment without pollution from other light sources. The sample surface is irradiated according to the set parameters. There are two treatments in this experiment: 1. Test the temperature changes of each group of samples after laser irradiation without any measures (i.e. directly test the dry samples). 2. Soak each group of samples in 300μL sterile PBS to simulate the physiological fluid environment in the body, and test the temperature changes of each group of samples after laser irradiation. At least three parallel samples are set up for each group for testing, and then the temperature change value per minute is recorded in real time and photographed with a thermal imager. Finally, the data and the highest value of temperature rise at the 10th minute of irradiation are recorded. In addition, in order to further explore the stability of photothermal conversion of the prepared material under near-infrared laser irradiation, we also selected the same photothermal parameters to detect the cyclic temperature changes of the BP@Sr group. In 5 laser on / off cycles, various photothermal data are recorded in real time. In addition, in order to explore the different photothermal effects of black phosphorus nanosheets with different concentrations, we loaded the samples with (0.25, 0.5, 1 mg / mL -1 ) of black phosphorus nanosheet suspension. The sample was immersed in 300 μL sterile PBS to observe the temperature change after being irradiated by laser.
[0078] Figure 6 The photothermal performance evaluation of black phosphorus nanosheets is shown. Figure 6 A refers to the set parameters (808nm, 1W / cm 2 Under the action of 10min, the highest temperature of each experimental group under dry conditions was 58.9℃ in the BP@Sr group. Figure 6 B is to test the highest temperature of each experimental group by immersing the sample in PBS, and the BP@Sr group can reach a maximum of 82.1℃. Figure 6 C verified that the photothermal conversion efficiency of black phosphorus nanosheets is related to its concentration and presents a positive correlation. Figure 6 D is the temperature rise curve of the samples in each experimental group in a dry environment. At the 6th minute, the temperature tended to be stable, and then slowly rose to reach the maximum temperature. Figure 6 E reflects and verifies the photothermal stability of the BP@Sr group material. After five laser on / off cycles, its photothermal stability is not affected. Figure 6 F shows the real-time photothermal images of each experimental group under near-infrared laser irradiation.
[0079] Example 3 Evaluation of in vitro osteogenic properties of BP@Sr coating
[0080] 1. Cell morphology
[0081] The shape of mature cells is closely related to their normal functional expression. Temperature, humidity, cell density, CO2 concentration, nutritional conditions, etc. will affect the normal growth of cells. MC3T3-E1 cells are spindle-shaped and radial under the microscope, so we used fluorescent staining on the cell skeleton and nucleus to observe the effect of each group of samples on the morphology of MC3T3-E1 cells. First, MC3T3-E1 cells were cultured at (0.8×10 4 The density of 100 μL / well was inoculated on the surface of each group of samples, and 6 parallel controls were set up in each group. The cells were placed in a 37°C constant temperature incubator with 5% CO2 for 3 days and then the original solution was discarded. After gently washing the cells 2-3 times along the wall with sterile PBS, 300 μL of 4% tissue cell fixative was added along the wall of each well and placed at room temperature for 30 minutes to complete cell fixation. After the cell fixation is completed, the fixative is discarded and the cells are gently washed 2-3 times with PBS to wash away the residual fixative. Subsequently, 0.1% Triton X-100 was added for 10 minutes to perform cell perforation to increase the penetration efficiency of subsequent fluorescent dyes, enhance the cell fluorescence effect, and facilitate microscopic observation. After the perforation treatment is completed, 300 μL of FITC-labeled phalloidin dye (100nM) is added to each well to stain the cytoskeleton for 60 minutes. After staining, wash each well 2-3 times with sterile PBS, and then add 300μL of DAPI dye (10μg / mL) to stain the cell nucleus for 10 minutes. All the above staining steps are performed in a light-proof environment. Then discard the liquid and gently rinse with sterile PBS to keep each well moist. Finally, under an inverted phase contrast microscope at 10x and 20x, five fields of view were randomly selected for each experimental group to photograph the cell morphology under fluorescence. Green fluorescence is the cytoskeleton and blue fluorescence is the cell nucleus. Take pictures, record and analyze.
[0082] Figure 7 A shows the morphological results of the cells. The blue represents the nucleus and the green represents the cytoskeleton. The cell morphological image results show that after 3 days of co-culture, the morphology of cells in each group spread to a certain extent and formed different numbers of filopodia. There is little difference between the groups.
[0083] 2. Cell viability test (CCK-8)
[0084] Cell viability can measure whether the material is biocompatible and is also the basis for cells to function. 4MC3T3-E1 cells were inoculated in each well at a density of 100 μL / well. α-MEM medium containing 10% FBS and 1% double antibody mixture was used to co-culture with the cells on the sample, and the medium was replaced every two days. The cell viability on the surface of the samples in each experimental group was detected after 4d and 7d to evaluate the biocompatibility of the samples. The subsequent operations of this experiment were all carried out under light-proof conditions. After the corresponding time detection point, the well plate was first placed in the clean bench to aspirate the original culture medium, and then 300 μL of α-MEM culture medium containing 10% CCK-8 solution and serum-free was added to each well along the wall. And incubated in a 37°C constant temperature incubator for 2h. Subsequently, 100 μL of culture medium containing CCK-8 was aspirated from each well and added to the 96-well plate to avoid absorbing bubbles. Then the absorbance of each group was detected at a wavelength of 450nm using an enzyme marker. Six replicate wells were set for each group in this experiment, and the CCK-8 test was repeated at least three times.
[0085] like Figure 7 The results of B and 7C show that the cell viability of the BP@Sr treated group was higher than that of the blank control group on the 4th day. After the 7th day of co-culture, the cells in each group grew to a certain extent, which was consistent with the cell morphology results, indicating that each group had good biocompatibility.
[0086] 3. Live / Dead cell staining experiment
[0087] In this experiment, (2×10 4 MC3T3-E1 cells were inoculated into each well at a density of 100 cells / well. α-MEM medium containing 10% FBS and 1% double antibody mixture was used for co-culture with the cells plated on the sample. After the 1st and 3rd days, the cells were observed under an inverted phase contrast fluorescence microscope after staining. The specific operation steps are as follows: First, Buffer×10mL was mixed with 10μL AM dye and 30μL PI dye under light-proof conditions. The original culture medium in the well plate was discarded, and then the mixed dye was added and reacted at room temperature for 5-6 minutes. Then observed under the microscope, and five fields of view were randomly selected from each group for photographing and recording.
[0088] The results are as follows Figure 8 As shown: the number of living cells (green) in each group of vision accounts for the vast majority, while there are only a few dead cells (red). This shows that the materials in each experimental group show excellent cell compatibility.
[0089] 4. BCIP / NBT alkaline phosphatase colorimetric test and evaluation of alkaline phosphatase (ALP / AKP) activity in cells
[0090] In the qualitative alkaline phosphatase staining assay, MC3T3-E1 cells were first plated at (2×10 4 / well) were counted and plated on different samples, and cultured with α-MEM medium containing 10% FBS and 1% double antibody mixture for 4d and 7d. Add sterile PBS to the cells cultured on the sample along the wall of the well plate and gently wash 2-3 times, then add 300μl of 4% paraformaldehyde to each well for fixation for 30min and rinse with sterile PBS 2-3 times. Then, under light-proof conditions, the pre-prepared color system solution: take 10mL of buffer, 33μL of bcip, and 66μL of nbt, mix well, and add 300μL to each well. After staining at room temperature for 1h, the stained samples were washed 1-2 times with deionized water to stop the color reaction, and observed under a stereo microscope. Six duplicate wells were set for each group, and five fields of view were randomly selected from each well for photographing and preservation.
[0091] In the quantitative alkaline phosphatase detection experiment of osteogenic induction, MC3T3-E1 cells (2×10 4 The cells were counted and plated on different samples (100 μg / well) and cultured for 4 and 7 days with α-MEM medium containing 10% FBS and 1% double antibody mixture. The ALP activity was determined using an alkaline phosphatase (ALP) detection kit. First, the cells at the time point to be tested were washed with sterile PBS solution, 1% Triton X-100 solution was added to cover the surface of the sample, and it was placed in a 4°C refrigerator for 40 minutes to react to lyse the cell membrane. This can release the protein in the cell. The lysate of each group was collected and centrifuged at 1200rpm for 10 minutes, and the supernatant was taken. ALP can convert colorless p-nitrophenyl phosphate (pNPP) into colored p-nitrophenol after incubation at 37°C for 30 minutes. After the reaction was terminated, the absorbance value was measured at a wavelength of 520nm and the AKP value of the sample was calculated. At the same time, the BCA standard curve was drawn, and the total protein concentration in the cell was measured at a wavelength of 562nm. Finally, the relative activity value of AKP in each group was calculated by the formula: AKP relative activity = ALP activity value of the sample to be tested / total protein concentration of the sample to be tested.
[0092] Alkaline phosphatase (ALP) activity represents the early osteogenic differentiation ability of cells. The qualitative staining and quantitative results were tested on the 4th and 7th days of osteogenic induction, respectively. Fig. 9 As shown in A. Compared with the Control group and PDPA group, the ALP expression of Sr, BP, and BP@Sr groups was significantly enhanced. Fig. 9 B. 9C, the ALP expression activity was the highest in the BP@Sr group.
[0093] 5. Extracellular Matrix Mineralization Assay
[0094] In the in vitro mineralization experiment, MC3T3-E1 cells were firstly cultured at (2×10 4The density count of cells / well) was plated on the sample surface, and the culture medium was replaced every two days. After continuous culture in a 37°C incubator for 21 days, the original culture medium was discarded, and the cell surface of each well was gently washed along the wall with sterile PBS, and then 300 μL of 4% tissue cell fixative was added to each well, which did not cover the cell surface. After fixing for 30 minutes, the cells were washed 2-3 times with deionized water. At room temperature, 300 μL of Alizarin Red S was added to each well for dyeing for 30 minutes, and then washed 3-5 times with deionized water until the washed liquid had no color precipitation. The images of mineralized nodules were observed and photographed with a stereo microscope adjusted to the appropriate multiples and light to obtain the best field of view under a wet state. Subsequently, 10% hexadecylpyridinium chloride solution was added, and the mineralized nodules on the surface were completely dissolved by heating, shaking, ultrasound and other methods, and then 150 μL was taken from each well to a 96-well plate. The absorbance value was measured at a wavelength of 540 nm in an ELISA instrument, which was the quantitative result of the mineralization experiment.
[0095] Matrix mineralization is considered an indicator of late osteogenic differentiation of cells. Fig.10 A Alizarin red staining results show that the effects of Sr, BP, and BP@Sr groups are better than those of the control group, with scattered small mineralized nodules (indicated by arrows). Fig.10 As shown in B, the BP@Sr group showed the best mineralization effect, which was better than other experimental groups and had a significant statistical difference from the Control group.
[0096] 6. Cell mineralization gene expression assay
[0097] In the osteogenic gene expression experiment, MC3T3-E1 cells were firstly cultured at (2×10 4The density of 1000 μL / well was counted and plated on the surface of the sample, and then placed in a 37°C incubator for 7 days, with the culture medium replaced every two days. After 7 days, the intracellular RNA was extracted using a total RNA extraction kit, that is, after the cells were lysed with 500 to 600 μL of Trizol lysis buffer, the intracellular protein and RNase were denatured, and the total RNA was retained in the upper aqueous phase after centrifugation, while most of the DNA and protein were retained in the middle phase or the lower aqueous phase. Then, the RNA was purified through multiple precipitation, centrifugation and washing processes, and finally the RNA was washed and stored with enzyme-free ultrapure water. The RNA concentration was determined using a NanoDrop 2000 spectrophotometer (A260 / A280≈1.8-2.0). The obtained RNA was reverse transcribed into cDNA using a PrimeScript RT kit, and the reverse transcription time was about 25 minutes. Finally, cDNA was amplified using a TB GreenTM Premix Ex TaqTM II kit on a real-time fluorescence quantitative PCR instrument. The target genes included alkaline phosphatase (ALP) and core binding factor 2 (RUNX2), and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as an internal reference gene. The relevant primer sequences are shown in Table 3.
[0098] Table 3 Osteogenesis-related primer sequences
[0099]
[0100] After 7 days of co-culture with cells, the expression levels of ALP, RUNX2, and OCN osteogenic-related genes in the four groups of Control / Sr / BP / BP@Sr were tested. Fig.10 As shown in B and 10C, compared with the Control group, the expression of osteogenic genes in the Sr / BP / BP@Sr group showed an upward trend, among which the expression level in the BP@Sr group was the highest.
[0101] Example 4 Evaluation of in vitro antibacterial properties of BP@Sr coating
[0102] 1. Bacterial plate
[0103] In the clean bench, place the samples of each experimental group face up in a 24-well plate, then add 500 μL of 75% ethanol solution to each well and soak for 1 hour. After the alcohol evaporates, blow dry to complete the sample disinfection. Set up at least 5 replicates for each group. S. aureus and E. coli stock solutions were diluted with sterile PBS to 1×10 7The density of CFU / mL was inoculated on each group of samples, and then placed in a constant temperature incubator at 37°C and 5% CO2 for incubation. After 4 hours of culture, the culture fluid of each group was discarded. Sterile PBS was added along the wall to wash the bacteria that were not attached to the surface of the sample, and then the samples were transferred to a new 24-well plate in turn. The efficiency of photothermal antibacterial was measured under the comparison of NIR(-) and NIR(+). The parameters for near-infrared light irradiation treatment on the sample surface are: 808nm, 1W / cm 2 , irradiation time is 10min. Then add 500μL sterile PBS to each well and place it in an ultrasonic cleaner for 5min to shake off the bacteria firmly attached to the sample surface. The eluate is diluted in a 48-well plate in sequence. To be diluted 1×10 4 After 100 μL was evenly spread on the LB agar plate with a pipette. The spread plates were marked, grouped, inverted and placed in a constant temperature incubator for 15 hours, and then the number of colonies formed on the plates was taken out and recorded. The antibacterial rate of each group of samples was measured by comparing the number of bacteria with the control group.
[0104] like Fig.11 and Fig.12 The plate count images and CFU statistics of each experimental group material after 4 hours of culture with S. aureus and E. coli are shown. Fig.11 The results of A and 12A plate counts show that under NIR(-) and NIR(+) treatments, the number of Staphylococcus aureus and Escherichia coli eluted from the BP / BP@Sr sample is less than that of the Control group, indicating that the number of Staphylococcus aureus and Escherichia coli adhering to the surface of the above two groups of samples, or growing and proliferating, is less than that of the Control group. The Control group always showed the largest number of bacteria. Through quantitative calculation, we can get: Fig.11 B and 11C / 12B and 12C show that photothermal treatment can assist in sterilization. The results of the antibacterial experiment prove that PDPA / Sr / BP / BP@Sr have different degrees of antibacterial effect without other treatments. At the same time, PDPA / Sr / BP / BP@Sr have different degrees of photothermal synergistic antibacterial ability, among which BP / BP@Sr shows superior synergistic photothermal antibacterial ability. The Control group has basically no antibacterial effect.
[0105] 2. Bacterial electron microscopy
[0106] In order to observe the morphology of bacteria in the control group and the BP@Sr group under the microscope, we first soaked the samples in 75% ethanol solution for 1 hour. After evaporation, we diluted the S. aureus and E. coli stock solutions with sterile PBS and added 1×10 7The density of CFU / mL was inoculated on the surface of the sample. Then it was placed in a constant temperature incubator at 37°C and 5% CO2 for incubation. After 4 hours of culture, the culture fluid of each group was discarded. Sterile PBS was added along the wall to wash the sample 1-2 times. The sample was then treated with NIR(+), and a control without any treatment was set up. Then it was placed in a 4°C refrigerator under light-proof conditions, and 2.5% glutaraldehyde solution was added to each well to cover the sample, and the bacteria on the surface of the sample were fixed overnight. Then it was washed with PBS 1-2 times, and dehydrated with (30%, 50%, 70%, 90% and 100%) alcohol gradients for 15 minutes each. Finally, the alcohol was replaced with hexamethyldisilane for 10 minutes, and the sample was dried for testing.
[0107] like Fig.13 A shows that the Staphylococcus aureus adhered to the surface of the sample in the Control group has a relatively complete and plump bacterial morphology. This shows that the untreated zirconium oxide lacks antibacterial ability. On the other hand, the Staphylococcus aureus adhered to the surface of the BP@Sr group material tends to be unfull and wrinkled. At the same time, near-infrared light NIR(+) irradiation and no treatment were applied for comparison. It can be seen that the Staphylococcus aureus after irradiation treatment is more obviously wrinkled and has an abnormal morphology. Fig.13 B It can be concluded that the same phenomenon exists in Escherichia coli. When observed under a microscope, Escherichia coli was mainly incomplete, darkened, and shrunken after being exposed to black phosphorus nanosheets. This shows that it has a contact antibacterial effect, and under NIR (+) contrast treatment, Escherichia coli showed more serious morphological changes such as dissolution, concavity, and fracture. The results of bacterial electron microscopy showed that the BP@Sr group has excellent antibacterial effects, and in addition, it can more efficiently ablate bacteria by synergizing with light and heat.
[0108] 3. Live / Dead staining of bacteria
[0109] This experiment mainly compares the antibacterial effects of the experimental group and the experimental group under NIR (+) conditions. First, the original bacterial solution of S. aureus and E. coli was diluted with sterile PBS and then 1×10 7The density of CFU / mL was inoculated on the surface of the sample. After 4h incubation, the sample was taken out and placed in a new 24-well plate, and 500μL of sterile PBS was added along the wall to rinse once. Then the same amount of PBS was added and ultrasonically treated in an ultrasonic cleaner for 5min. The eluate was then collected in an EP tube, placed in a centrifuge, and centrifuged at 3000rpm for 5min. After centrifugation, the eluted bacteria were obtained. Then the biofilm was stained with the fluorescent nucleic acid stain SYTO-9 to detect live bacteria. Cell damage nucleic acid stain propidium iodide (PI) was used to detect dead bacteria. After staining at room temperature in the dark for 30min, it was centrifuged and rinsed 3 times with deionized water, and finally 1-2μL of bacterial solution was taken and placed on a slide for observation under an inverted fluorescence microscope. Each sample was photographed and recorded in five different directions.
[0110] like Fig.14 The following are the results of bacterial live and dead staining in each experimental group. The blank control group and the BP@Sr group showed obvious inhibition of Staphylococcus aureus and Escherichia coli under the action of NIR(+), which was consistent with the results of CFU and bacterial electron microscopy.
[0111] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A dopamine-doped BP@Sr coating that promotes bone formation and is antibacterial, wherein the dopamine-doped BP@Sr coating is used to modify inert interventional medical devices, and the preparation method of the dopamine-doped BP@Sr coating is: (1) preparing a 0.1-5 mg / ml dopamine solution, adjusting its pH to alkaline, and completely immersing an inert interventional medical device in the dopamine solution for 24 hours to form a polydopamine coating on the surface of the inert interventional medical device; (2) immersing the inert invasive medical device modified with the polydopamine coating in a mixed solution of 50 wt % polyallylamine and NaOH for 12 h to perform amino-rich modification; (3) adding a strontium salt solution of the same volume ratio and immersing for 12 hours to fix the strontium ions on the surface of the dopamine coating; (4) Prepare 0.1-1.5 mg / mL -1 Black phosphorus suspension, immersing the coating obtained in step (3) in the black phosphorus suspension, treating in a vacuum negative pressure drying oven for 6 hours, loading black phosphorus nanosheets through strong electrostatic bonding, and obtaining the dopamine-doped BP@Sr coating.
2. The dopamine-doped BP@Sr coating according to claim 1, characterized in that: The mass concentration of the NaOH is 2-10 mg / ml, and further, the mass concentration is preferably 6 mg / ml.
3. The dopamine-doped BP@Sr coating according to claim 1, characterized in that: The step (1) can be repeated 1-9 times to prepare 2-10 layers of polydopamine coating.
4. The dopamine-doped BP@Sr coating according to claim 1, characterized in that: The concentration of the dopamine solution is 1 mg / ml; optionally, the pH of the dopamine solution is adjusted to 8-10, preferably adjusted to 9.
5. The dopamine-doped BP@Sr coating according to claim 1, characterized in that: The strontium salt comprises one or more of strontium chloride, strontium bromide, strontium iodide and strontium nitrate, preferably strontium chloride; optionally, the mass concentration of the strontium salt is 5-40 mg / ml, preferably 20 mg / ml.
6. The dopamine-doped BP@Sr coating according to claim 1, characterized in that: The concentration of black phosphorus is 0.5 mg / mL -1 .
7. An inert interventional medical device, wherein the inert interventional medical device is modified with the dopamine-doped BP@Sr coating according to any one of claim 16.
8. The inert interventional medical device according to claim 7, characterized in that: The interventional medical device is a dental implant, an artificial joint, an artificial heart valve or an interventional cardiovascular stent, preferably a dental implant.
9. The inert interventional medical device according to claim 8, characterized in that: The material of the dental implant is pure titanium, titanium alloy, zirconium oxide or carbon, preferably zirconium oxide.
10. Use of the dopamine-doped BP@Sr coating according to any one of claims 1 to 6 in the preparation of osteogenic and antibacterial products.
Citation Information
Cited By
Coating for modifying dental restoration material, application and dental restoration material
CN120695260A